Sex differences in renal cell carcinoma: a single-cell analysis reveals exhausted CD8+ T-cells highly infiltrated in males - Kang Ning; Yulu Peng; Yue Jiang; Zhen Li; Xin Luo; Lede Lin; Minhua Deng; Yi Wu; Tingxuan Huang; Yixin Huang; Ye Xie; Xiaofeng Yang; et al. (Biology of Sex Differences, 2023)
Abstract Background Although sex bias has been reported in the development and progression of renal cell carcinoma (RCC), the underlying mechanisms remain enigmatic. Here, we investigated the sex differences in the tumor microenvironment (TME) of RCC and explored a promising combination drug regimen to enhance the efficacy of immunotherapy. Methods Single-cell RNA sequencing (scRNA-seq) data from four published datasets were analyzed to investigate the sex differences in RCC patients, and tumor tissues were collected to validate the sex differences using multiplex immunofluorescence (MxIF) and flow cytometry (FCM). The function of the androgen–androgen receptor axis in sex differences was explored in vivo and in vitro experiments. Results Our analysis of scRNA-seq data from 220,156 cells, as well as MxIF and FCM assays, revealed that CD8+ T-cells infiltrated highly in the TME of male RCC, but were mostly in an exhausted and dysfunctional state. In vitro and in vivo experiments indicated that the dysfunction and exhaustion of CD8+ T-cells in male TME were induced by androgen. Clinically, higher serum androgen was significantly associated with a worse prognosis in male RCC patients receiving immunotherapy. Androgen receptor inhibitors could activate tumor-infiltrating CD8+ T-cells and enhance the efficacy of immunotherapy of RCC in vivo. Conclusions Our study delineated the difference in TME between male and female patients with RCC, and demonstrated that the androgen–androgen receptor axis plays an important role in immunosuppression in male RCC. Our findings suggest that androgen receptor inhibitors in combination with immunotherapy may be a promising treatment option for male RCC patients.